2019
DOI: 10.1093/ptj/pzz093
|View full text |Cite
|
Sign up to set email alerts
|

Is Virtual Reality Effective in Orthopedic Rehabilitation? A Systematic Review and Meta-Analysis

Abstract: Background Virtual reality (VR) is an interactive technology that allows customized treatment and may help in delivering effective person-centered rehabilitation. Purpose The purpose of this review was to systematically review and critically appraise the controlled clinical trials that investigated VR effectiveness in orthopedic rehabilitation. Data Sources P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 48 publications
2
75
0
Order By: Relevance
“…As far as the authors are concerned, this is the first randomized clinical trial that has studied the use of VR for NS-CNP and compared pain-related, motor and psychological outcomes compared to an exercise group in the short-term. Recent reviews have concluded that more research is needed regarding VR as a treatment of musculoskeletal disorders [24,26,65]. The present study matches the protocol of the reviewed articles where the treatment was delivered during four weeks of chronic pain, with similar immediate results [65].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As far as the authors are concerned, this is the first randomized clinical trial that has studied the use of VR for NS-CNP and compared pain-related, motor and psychological outcomes compared to an exercise group in the short-term. Recent reviews have concluded that more research is needed regarding VR as a treatment of musculoskeletal disorders [24,26,65]. The present study matches the protocol of the reviewed articles where the treatment was delivered during four weeks of chronic pain, with similar immediate results [65].…”
Section: Discussionmentioning
confidence: 57%
“…Although other studies have failed to demonstrate a hypoalgesic effect of distraction, the majority of studies have shown that distraction does reduce pain, most of them in acute conditions [25]. A meta-analysis published in 2019 [26] showed that VR applied to patients with neck pain was promising in producing positive effects when applied alone or combined with exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant body of research exists on the use of VR for acute pain management [ 26 , 28 , 30 , 52 - 54 ] and for physical rehabilitation [ 24 , 40 ], the use of VR as a platform to deliver behavioral medicine for chronic pain remains novel and understudied. Research on VR for acute pain is based on the premise that distraction is a primary mechanism of VR analgesia [ 33 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Promising studies have used VR to reduce pain and improve outcomes in complex regional pain syndrome [ 34 ], chronic headache/migraine pain [ 35 ], fibromyalgia [ 36 , 37 ], and chronic musculoskeletal pain [ 38 , 39 ]. Two recent reviews and meta-analyses reported the efficacy of VR for physical rehabilitation from painful spinal conditions [ 24 ] and for orthopedic rehabilitation in terms of reduced pain and disability [ 40 ]. In such studies, the user may engage with interactive VR alone or within the context of kinematic training.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials have assessed VR effectiveness in patients with orthopaedic pathology such as ACL injury, frozen shoulder and chronic neck pain. Most of them used off-the-shelf console games such as Nintendo Wii Fit, making it difficult to differentiate from rehabilitation using CAGS [70].…”
Section: The Futurementioning
confidence: 99%